Perancangan Kap Lampu Hias dengan Material Tembus Cahaya - Reny Karina Claudia (Intra, 2017)
Human need light for everyday activity and because of that lamp is necesary for human life. With technology advancement, many type of lamp is created, like LED lamp which in demand right now because this lamp is bright, light, cheap, and did not emmit heat. Not only lamp, technology also make advancement in material product. May type of material can be choosen to make desain more vibrant. This advancement make desain that not possible to be made previouslyy to be possible now. Because of that right now, lamp not only be use for lighting but also for decorative purpose.